2014
DOI: 10.1098/rsif.2014.0283
|View full text |Cite
|
Sign up to set email alerts
|

Topological properties of robust biological and computational networks

Abstract: Network robustness is an important principle in biology and engineering. Previous studies of global networks have identified both redundancy and sparseness as topological properties used by robust networks. By focusing on molecular subnetworks, or modules, we show that module topology is tightly linked to the level of environmental variability (noise) the module expects to encounter. Modules internal to the cell that are less exposed to environmental noise are more connected and less robust than external modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 60 publications
1
30
0
1
Order By: Relevance
“…On the other hand cell wall organization, endosomal transport are examples of external cell processes less connected and not enriched for essential genes [117]. Even though this study is focused on Saccharomyces cerevisiae authors note similar results for other organisms including bacteria and roundworm and even identified similarities to the computational systems security [117]. Therefore, those findings might be generally applicable.…”
Section: Therefore We Have Proceed To Identify Disease Modules Basedmentioning
confidence: 81%
See 4 more Smart Citations
“…On the other hand cell wall organization, endosomal transport are examples of external cell processes less connected and not enriched for essential genes [117]. Even though this study is focused on Saccharomyces cerevisiae authors note similar results for other organisms including bacteria and roundworm and even identified similarities to the computational systems security [117]. Therefore, those findings might be generally applicable.…”
Section: Therefore We Have Proceed To Identify Disease Modules Basedmentioning
confidence: 81%
“…Indeed sparser net-works are shown to be more robust [118]. Interestingly in [117] it is shown that modules exposed to greater environmental variation are generally more robust and contain less interactions [117]. On the other hand more essential modules (i.e.…”
Section: Therefore We Have Proceed To Identify Disease Modules Basedmentioning
confidence: 99%
See 3 more Smart Citations